Does Seeing What Others Do Through Social Media Influence Vaccine Uptake and Help in the Herd Immunity Through Vaccination? A Cross-Sectional Analysis - Al-Hasan, Abrar; Khuntia, Jiban; Yim, Dobin (Frontiers in Public Health, 2021)
Widespread acceptance of COVID-19 vaccination is the next major step in fighting the pandemic. However, significant variations are observed in the willingness to take the vaccination by citizens across different countries. Arguably, differences in vaccination intentions will be influenced by beliefs around vaccines to influence health. Often perceptions of what others are doing and the information available guide individuals' behaviors for vaccination. This is more so in the digital age with the influence of the internet and media. This study aims to determine the factors that impact willingness to vaccinate for COVID-19. We examined factors associated with acceptance of vaccine based on (1) constructs of the Health Belief Model (HBM), (2) sources of information, (3) social media usage, (4) knowledge of COVID-19 treatment, and (5) perception of government's efforts for mitigation. Randomly sampled online survey data was collected by a global firm between December 2020 and January 2021 from 372 citizens (with a response rate of 96.6%) from multiple regions, including North America, the Middle East, Europe, and Asia. Ordered probit regression suggests that the health belief model constructs hold. Perceived severity of COVID-19 (P < 0.001) and action cues of others taking the vaccine positively influences a subject's vaccine intent (P < 0.001), perceived benefits and perceived efficacy of the vaccine positively influences a subject's vaccine intent (P < 0.001). Perceived barriers negatively influence vaccine intent (P < 0.001). Interestingly as for media usage, mainstream media (e.g., TV, newspaper) (P = 0.006) and social media (P = 0.013) both negatively influence a subject's vaccine intent. Social media platforms that are more entertainment and social-based, such as Whatsapp, Instagram, and YouTube, have a negative and significant influence on vaccine intent (P = 0.061), compared to other more information-based social media platforms (e.g., Twitter, LinkedIn). Knowledge of COVID-19 treatment positively influences vaccine intent (P = 0.023). Lastly, governmental efforts' perceived reliability in mitigation strategy (P = 0.028) and response efforts (P = 0.004) negatively influence vaccine intent. The study highlights the “wait-and-see” action cue from others and leaders in the community. It also informs the importance of shaping media information for vaccination through informative media and social media outlets to counteract any misinformation.